JELGAVA AS A CONCERT VENUE IN THE 19TH CENTURY: MUSICIANS AND REPERTOIRE (Mūzikas akadēmijas raksti, 2024)
Until now, the historiography of Jelgava has been more extensively focused on the history of the Duchy of Courland and Semigallia, invariably as a residence of Baroque architecture and sculpture, later also as a bearer of Classical cultural heritage, an ancient theatre town where many well-known plays were staged and performed, the history of the Latvian theatre additionally brought into this field of performances. But, what can we highlight when we talk about Jelgava (in German – Mitau) as a concert venue in the 19th century? During the existence of the Duchy and later, Jelgava was home to many foreign musicians who brought a high level of musical culture and thanks to whom, the city became one of the centres of musical life in the territory of Latvia.